Integrating SDG 4: The Influence of Family and Interests on Students’ Decisions in Choosing Cross-Interest Economics Programs - Maychella Laurencia; Riza Yonisa Kurniawan (Journal of Psychology and Culture Behavior in SDGs, 2026)
Objective: This research aims to analyse the partial influence of family and student interest on the decision to choose an interdisciplinary economic programme in line with SDGs. Method: This research is quantitative in nature, using an online questionnaire distributed to students at SMAN 1 Mojosari through purposive sampling with a total sample of 69. The data analysis technique employed SEM-PLS assisted by WarpPLS. Results: The study found that external aspects such as family do not affect the decision to choose an interdisciplinary economic programme, while internal factors, namely interest, have a positive and significant effect. Novelty: The research emphasises the integration of SCCT theory and a previously unexamined population. The latest contribution is that schools should focus on strengthening and adapting interdisciplinary programmes to prioritise the students' own capabilities. Furthermore, this research reflects new knowledge about the self-efficacy of today's students who are already able to convince their parents about career and study paths in accordance with their interests.